DO GENDER DIVERSITY AND CEO CULTURE AFFECT SUSTAINABILITY PERFORMANCE IN THE NIGERIAN BANKING INDUSTRY? - Idris Adamu, Adamu; Yusuf, Ismaila; Jinjiri Bala, Ahmed (Bank Indonesia, 2024)
This study investigates how gender diversity and CEO culture affect sustainability performance in the banking industry. The sample used in the study was drawn from listed banks on the floor of the NGX group. The data were obtained from the Bloomberg Database with 88 firm-year observations (2011 to 2018). The regression estimate is based on a panel data approach. We found that female directors’ and CEOs’ cultures have greater tendencies to enhance sustainability performance proxied by ESG. Thus, the findings provide additional insight into the existing literature on sustainability and diversity initiatives as well as the resource dependency theory. It also adds to the existing literature on sustainability reporting. The findings, moreover, allude to the initiatives of the regulatory authority in the industry that emphasise the need to have a diversified board that includes female directors and other forms of diversity, for example, ethnicity.